Kesetaraan Gender sebagai Pilar Pembangunan Masyarakat: Tantangan, Strategi, dan Rekomendasi Kebijakan - Yanti, Fitri; Ramadhani, Mutiara; Haq, Fauzi Nadziiran; Pratiwi, Devi Tias (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
This study aims to analyze gender issues in community development by highlighting the role and participation of women in Indonesia. Gender inequality remains a serious barrier to inclusive development, particularly in terms of access to education, employment, health services, and political representation. The research employs a descriptive mixed methods approach, combining document analysis and secondary quantitative data. Qualitative data were obtained from policy documents and reports published by the Ministry of Women’s Empowerment and Child Protection, the Central Bureau of Statistics, and international organizations. Meanwhile, quantitative data, including the Gender Development Index (GDI), Gender Empowerment Index (GEI), and indicators of women’s participation in various development sectors, were utilized to illustrate the factual conditions. The analysis is grounded in the theoretical framework of gender and development, which emphasizes equal access and opportunities as prerequisites for sustainable development. The findings reveal that although there has been progress in women’s participation, structural gaps remain significant, particularly those shaped by cultural norms and gender stereotypes. Gender mainstreaming policies have been introduced, yet their implementation at the local level remains limited. This study concludes that gender mainstreaming should be regarded as a key strategy for community development in Indonesia. Future research is recommended to examine best practices of gender mainstreaming at the local level and to conduct comparative studies across regions to identify effective patterns. Thus, this study contributes to strengthening the discourse on gender equality while providing empirical foundations for the formulation of more inclusive development policies. Keywords: gender equality; community development; women’s participation; gender mainstreaming; Indonesia